Intimacy in Phone Conversations: Anxiety Reduction for Danish Seniors with Hugvie - Yamazaki, Ryuji; Christensen, Louise; Skov, Kate; Chang, Chi-Chih; Damholdt, Malene F.; Sumioka, Hidenobu; Nishio, Shuichi; Ishiguro, Hiroshi (Frontiers in Psychology, 2016)
There is a lack of physical contact in current telecommunications such as text messaging and Internet access. To challenge the limitation and re-embody telecommunication, researchers have attempted to introduce tactile stimulation to media and developed huggable devices. Previous experiments in Japan showed that a huggable communication technology, i.e., Hugvie decreased stress level of its female users. In the present experiment in Denmark, we aim to investigate i) whether Hugvie can decrease stress cross-culturally, i.e. Japanese vs. Danish participants ii), investigate whether gender plays a role in this psychological effect (stress reduction) and iii) if there is a preference of this type of communication technology (Hugvie vs. a regular telephone). Twenty-nine healthy elderly participated (15 female and 14 male, M=64.52 years, SD=5.67) in Jutland, Denmark. The participants filled out questionnaires including State-Trait Anxiety Inventory (STAI), NEO Five Factor Inventory (NEO-FFI) and Becks Depression Inventory (BDI-II), had a 15 minutes conversation via phone or Hugvie and were interviewed afterwards. They spoke with an unknown person of opposite gender during the conversation; the same two conversation partners were used during the experiment and the Phone and Hugvie groups were equally balanced. There was no baseline difference between the Hugvie and Phone groups on age or anxiety or depression scores. In the Hugvie group, there was a statistically significant reduction on state anxiety after meeting Hugvie (p=.013). The change in state anxiety for the Hugvie group was positively correlated with openness (r=.532 p=.041) as measured by the NEO-FFI. This indicates that openness to experiences may increase the chances of having an anxiety reduction from being with Hugvie. Based on the results, we see that personality may affect the participants’ engagement and benefits from Hugvie. We discuss the implications of the results and further elaborations.